Task assignments matter: The relationship between illegitimate tasks, work engagement and silence - Koçak, Ömer Erdem; Ünal, Zeynep Merve (Inderscience Publishers, 2022)
This study aims to investigate whether assigning employees to unnecessary or unreasonable tasks can harm employee motivation. To account for the full range of motivation, we examined how illegitimate tasks affect work engagement and employee silence. We also embraced interactional justice to propose a possible underlying mechanism. Online questionnaires were used to collect data from 250 white-collar employees from various industries, of which 55.2% were males and mean age was 33.64 (s.d. = 11.56). We used structural equation modelling to analyse the data. Illegitimate tasks were associated with lower work engagement and higher employee silence, as expected. The relationship between illegitimate tasks and work engagement was fully mediated by interactional justice while the relationship between employee silence and illegitimate tasks were partially mediated. These findings emphasise the negative impact of inappropriate tasks on employee motivation. This study shows that illegitimate tasks are crucial determinants of employee motivation of both approach and avoidance in Turkish work context.
Keywords: Employee Silence; Illegitimate Tasks; Interactional Justice; Motivation; Organisational Justice; Stress; Work Engagement